2010
DOI: 10.1002/pip.1056
|View full text |Cite
|
Sign up to set email alerts
|

Performance comparison of AlGaAs, GaAs and InGaP tunnel junctions for concentrated multijunction solar cells

Abstract: Four tunnel junction (TJ) designs for multijunction (MJ) solar cells under high concentration are studied to determine the peak tunnelling current and resistance change as a function of the doping concentration. These four TJ designs are: AlGaAs/AlGaAs, GaAs/GaAs, AlGaAs/InGaP and AlGaAs/GaAs. Time‐dependent and time‐average methods are used to experimentally characterize the entire current–voltage profile of TJ mesa structures. Experimentally calibrated numerical models are used to determine the minimum dopin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(49 citation statements)
references
References 18 publications
0
49
0
Order By: Relevance
“…TJ requirements of low resistance and high transparency oppose each other, as per the theoretical dependence of the peak tunneling current [9]: where a higher bandgap increases transparency but also reduces the peak tunneling current. It has been suggested that a GaAs/AlGaAs TJ with Al content of either 10% [10] or 30% [9,11], or AlGaAs/AlGaAs TJs with Al content <20% [9] can provide an acceptable tradeoff between low resistance and transparency.…”
Section: Tj Designmentioning
confidence: 99%
See 4 more Smart Citations
“…TJ requirements of low resistance and high transparency oppose each other, as per the theoretical dependence of the peak tunneling current [9]: where a higher bandgap increases transparency but also reduces the peak tunneling current. It has been suggested that a GaAs/AlGaAs TJ with Al content of either 10% [10] or 30% [9,11], or AlGaAs/AlGaAs TJs with Al content <20% [9] can provide an acceptable tradeoff between low resistance and transparency.…”
Section: Tj Designmentioning
confidence: 99%
“…These simulations are similar to those described in [9], but used a dynamic nonlocal-path direct band-to-band tunneling model [18], in combination with a nonlocal-path trap-assisted tunneling model [18]. In each of the simulations, the density-of-states effective mass is used for the conduction band and the valence band.…”
Section: Tj Characterizationmentioning
confidence: 99%
See 3 more Smart Citations